To Review and Compare Evolutionary Algorithms in Optimization of Distributed Database Query - Abdalla, Mohammed Hussein; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2020)
Processing queries in distributed databases require the conversion and transmission of data from local and global sites. A query can be used to create a different executive plan of the query, which these plans are equal in size, meaning that they achieve the same result, but differ in the order in which the operators are executed and how they are executed, and therefore in their performance. The problem of query optimization in the distributed database is NP-hard in nature and difficult to solve. Exploring all the query plans in large search space is not feasible. The purpose and motivation of this paper are to examine the query challenges in the distributed databases and algorithms for the executive plan of the query. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: Distributed Database; Evolutionary Algorithms; Query optimization; Search Strategy